Crises and Liquidity : Evidence and Interpretation - Detragiache, Enrica (IMF Working Papers; Working Paper ;, 2001)
In a large panel of countries, we find that less liquid countries are more likely to default on their external debt. Specifically, for given total external debt, the probability of a crisis increases with the proportion of short-term debt and debt service coming due and decreases with foreign exchange reserves. This correlation, however, is consistent with a standard model of optimal default and need not be ascribed to self-fulfilling creditor runs. Also, the correlation with short-term debt appears to be driven by joint endogeneity. The policy implications are discussed.